Rabies and African bat lyssavirus encephalitis and its prevention - (:unkn) unknown (My University, 2010)
Unlike any other human infection, encephalitis caused by dog rabies virus is always fatal. Rabies and other lyssaviruses have been found in unexpected places, and human disease, especially paralytic rabies, has gone unrecognized. Evidence is emerging that rabies-related bat lyssaviruses are enzootic across Europe, Africa, Asia and Australia, but none has been detected in the Americas. The epidemiology and origins of African lyssaviruses are discussed. Ideal rabies prophylaxis (pre-exposure immunization followed by post-exposure booster vaccination) has proved 100% effective; hence all human deaths result from failure of prevention. Rabies vaccines of known quality are unaffordable for the majority in Africa. Although intradermal regimens requiring <40% of the usual vaccine dose are economical and are recommended by the World Health Organization, several problems have inhibited their use. A new, simplified, economical post-exposure vaccine regimen that uses an initial dose of intradermal injections at four sites overcomes many of the difficulties of the previous methods: it is at least as immunogenic as the standard intramuscular course of tissue-culture vaccine; is safer in inexperienced hands; requires fewer than two ampoules of vaccine and only three instead of five clinic visits. Recent data should increase the confidence of physicians to use the World Health Organization-accredited rabies vaccines more efficiently and at lower cost.
Keywords: African Research